2020
DOI: 10.15390/eb.2020.8870
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Engineering-Oriented STEM Integration Activities on Scientific Process Skills and STEM Career Interests: A Mixed Methods Study

Abstract: STEM eğitimi gerçek dünya sorunlarının ele alındığı, birden çok duyu organının harekete geçirildiği (Bagiati ve Evangelou, 2015), hayallerin geliştirildiği, öğrenilenlerin yeni ve farklı durumlarda uygulanıldığı (Tseng, Chang, Lou ve Chen, 2013) pedagojik bir yaklaşımdır. Öğrencilere bir konuyla ilgili parça parça bilgi öğrenmesi yerine içinde yaşadıkları dünyayı anlamlandırma fırsatı sunan STEM eğitimi (Dugger, 2010), STEM disiplinlerinden en az birinin merkeze alınarak öğrencilerin bilgi, beceri ve deneyimle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…This proved that the implementation of inquiry activities with the 5E model had a positive impact on students' attitude toward chemistry as a subject. These findings indicate that teaching with the 5E model influences students' attitudes on the importance of chemistry and science in general, which is in line with other studies (e.g., Aguilera & Perales-Palacios, 2020;Bezen & Bayrak, 2020;Guven et al, 2020;Guzel, 2017;Jiang & McComas, 2015;Kang & Keinonen, 2017;Lin et al, 2014;Nicol et al, 2022;Ozkul & Ozden, 2020;Potvin et al, 2017;Savelsbergh et al, 2016;Wiriani & Ardana, 2022). The positive effect of IBSE on the "affective" results such as students' attitude to learning science was also identified by Ergul et al (2011), Gibson and Chase (2002), Potvin and Hasni (2014), and Wolf and Fraser (2008).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This proved that the implementation of inquiry activities with the 5E model had a positive impact on students' attitude toward chemistry as a subject. These findings indicate that teaching with the 5E model influences students' attitudes on the importance of chemistry and science in general, which is in line with other studies (e.g., Aguilera & Perales-Palacios, 2020;Bezen & Bayrak, 2020;Guven et al, 2020;Guzel, 2017;Jiang & McComas, 2015;Kang & Keinonen, 2017;Lin et al, 2014;Nicol et al, 2022;Ozkul & Ozden, 2020;Potvin et al, 2017;Savelsbergh et al, 2016;Wiriani & Ardana, 2022). The positive effect of IBSE on the "affective" results such as students' attitude to learning science was also identified by Ergul et al (2011), Gibson and Chase (2002), Potvin and Hasni (2014), and Wolf and Fraser (2008).…”
Section: Discussionsupporting
confidence: 89%
“…It promotes the development of critical thinking and argumentation skills, as well as the ability to apply the knowledge in practice (Amaliyah et al, 2023;Cahyarini et al, 2016;Chen, 2021;Chu et al, 2017;Ha et al, 2023;Miarti et al, 2021;Vafaeikia et al, 2023). It also facilitates the development of inquiry skills or scientific process skills (Cakir, 2017;Ergul, 2011;Harlen, 2021;Ješková et al, 2022;Liu et al, 2021;Ozkul & Ozden, 2020;Tolba & Al-Osaimi, 2023;Wale & Bishaw, 2020) such as formulation of research questions and hypotheses, provision of evidence, evaluation of explanations, and conclusion-drawing. Moreover, the 5E model promotes the development of scientific literacy (Areepattamannil et al, 2020;Bybee, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…STEM as an approach that is used as a basis for developing learning activities in modules becomes an embodiment process that can describe real learning concepts for students and improve the quality of learning. Besides that, it can direct students' interests and relate them to students' future career concepts (Farach et al, 2021;Özkul & Özden, 2020;Verawati et al, 2014). Science process skills are fundamental skills that students must acquire during the learning process in order to perform scientific work.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies in the literature on the development of SPSs (Yıldırım et al, 2016). While SPSs are taught explicitly in a relatively small proportion of these studies (Durmaz & Mutlu, 2012), they are implicit in a relatively large proportion of them (Bodur & Yıldırım, 2018;Çakiroğlu et al, 2020;Harahap et al, 2019;Özkul & Özden, 2020;Uysal & Cebesoy, 2020). In both approaches to teaching skills, it was found that the SPSs of the participants mostly improved.…”
Section: Discussionmentioning
confidence: 99%